2020
DOI: 10.3390/su12020624
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Collaborative Innovation between Research Institutions and Seed Enterprises in China

Abstract: Public research institutions are encouraged to engage in industry sustainable collaboration in China. We develop an analytical framework based on the factor-process-outputs model and use a mechanism model by incorporating four elements (innovation climate, strategic partnership, collaborative mechanism, and the degree of participation) associated with the research institutions and industry collaboration. Using data collected from a face-to-face interview survey of 533 experts located at research institutions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Capabilities (Oi 2004 ; Kwan and Chiu 2015 ; Styhre and Remneland-Wikhamn 2016 ; Cestino and Berndt 2017 ; Gehman and Höllerer 2019 ; Yu et al 2020 ; Khan and Gulati 2021 )…”
Section: Main Determinants Of Institutional Innovationmentioning
confidence: 99%
“…Capabilities (Oi 2004 ; Kwan and Chiu 2015 ; Styhre and Remneland-Wikhamn 2016 ; Cestino and Berndt 2017 ; Gehman and Höllerer 2019 ; Yu et al 2020 ; Khan and Gulati 2021 )…”
Section: Main Determinants Of Institutional Innovationmentioning
confidence: 99%
“…The focus of relevant studies lies in the university-industry (UI) collaboration [28], which is found beneficial for both universities [11] and industries [29]. On one hand, industries tend to persistently collaborate with universities, and such persistency is reported to associate with openness to innovation [30].…”
Section: Universities In Research Collaborationmentioning
confidence: 99%
“…Hence, it relies heavily on large seed industry enterprises, which play a central role in the innovation, production, and dissemination of new agricultural varieties. The direction of their research and development, pricing of varieties, and after-sales services are crucial to the widespread adoption of new seeds [49][50][51]. However, there is an inherent contradiction between the commercial objectives of seed industry enterprises and the livelihood goals of smallholders [52][53][54].…”
Section: Introductionmentioning
confidence: 99%